Video Game Localization: A Case Study of the Translation of Bully - Ardi Nugroho (Universitas Bunda Mulia, 2017)
Many forms of entertainment that we enjoy here in Indonesia such as movies. books, music, and even video games, often come from abroad, more specifically the U.S. Although movies and books are often officially translated and localized, this is not the case for video games. With the increasingly growing market of video games and number of gamers in Indonesia, very few games have started to be “localized” and translated into Indonesian. One such game is the Playstation 2 game Bully.All in all, the translation of the game Bully is a decent attempt to localize western video games. Seeing as the translation was not done by professional translators, the overall translation of the game was fairly good, with some problems here and there. It fulfilled its communicative purpose in the sense that the translation was comprehensible enough to play the game and understand the main story. The biggest problem lies in the translation of the dialogues that basically tells the whole story of the game. Some of the dialogues were poorly translated, especially those containing sensitive cultural materials that were difficult to translate. Even though the main story can be fairly understood in general, some of the dialogues were translated rather badly, making the flow from one utterance to the next not very smooth and disjointed at times. Keywords: translation, localization, cultural materials